EFFECTS OF AIRFLOW LIMITATIONS AND TRAINING STATUS ON GAS EXCHANGE AND HEART RATE RECOVERY KINETICS IN ELDERLY SUBJECTS (Sciences & Technologie. C, Biotechnologies, 2003)
To determine whether disease and training status results in different recovery kinetics of gas exchange and heart rate response in elderly subjects, 12 healthy control subjects, 18 patients with chronic obstructive pulmonary disease and 12 master athletes were examined during the five-minute recovery from maximal graded exercise. The recovery rate constants of oxygen uptake (VO2), carbon dioxide production (VCO2), ventilation (VE), and heart rate (HR) were fitted by a one-exponential model. Nonlinear regression showed that COPD exhibited a significantly slower recovery decay than CS for (VO2), (VCO2) and (VE), whereas HR recovery appeared to be unaffected by the disease status compared to controls. MA recovered faster than CS, except for (VE) recovery decay. We also demonstrated that the gas exchange and heart rate recovery kinetics were independent of maximal exercise work rate. We conclude that training generally improved the recovery responses in elderly subjects in contrast to the status of respiratory disease